2022
DOI: 10.3390/molecules27228093
|View full text |Cite
|
Sign up to set email alerts
|

Biotechnology and In Vitro Culture as an Alternative System for Secondary Metabolite Production

Abstract: Medicinal plants are rich sources of bioactive compounds widely used as medicaments, food additives, perfumes, and agrochemicals. These secondary compounds are produced under stress conditions to carry out physiological tasks in plants. Secondary metabolites have a complex chemical structure with pharmacological properties. The widespread use of these metabolites in a lot of industrial sectors has raised the need to increase the production of secondary metabolites. Biotechnological methods of cell culture allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 176 publications
(174 reference statements)
0
16
0
Order By: Relevance
“…A number of studies have revealed a preventive effect of PCs against these diseases [ 49 , 50 , 51 ]. In vitro systems of cultivation of various plant species can be an alternative source of polyphenolic compounds having a strong antioxidant effect, even stronger than that of intact plants [ 52 , 53 ]. Here, we investigated concentrations of PCs in the water-ethanol extract of S. pallasii microshoots ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of studies have revealed a preventive effect of PCs against these diseases [ 49 , 50 , 51 ]. In vitro systems of cultivation of various plant species can be an alternative source of polyphenolic compounds having a strong antioxidant effect, even stronger than that of intact plants [ 52 , 53 ]. Here, we investigated concentrations of PCs in the water-ethanol extract of S. pallasii microshoots ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Polyphenolic compounds are also important constituents of A. millefolium extracts, influencing, for example, their antioxidant activities [ 25 , 26 ]. One of the challenges connected with in vitro plant culture is a low level of bioactive compounds due to the lack of environmental stressors inducing their biosynthesis [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“… NaCl Solanum khasianum HRC 100 mM Alkaloid Ajmalicine 14.8-fold; 0.058 mg/g DW [ 27 ] 4. Chitosan Lepidium sativum Callus culture 250 mg/L Imidazole alkaloid Lepidin 19.87-fold [ 28 ] 5. GA3 Lepidium sativum Callus culture 2 mg/L Imidazole alkaloid Lepidin 3.89-fold [ 29 ] 6.…”
Section: Criterion Of Elicitorsmentioning
confidence: 99%